Evaluation of the Area of the Lisfranc Ligament Damaged by Screw Fixation. Issue 1 (February 2019) - Fernandez, Isaac; Weiss, William M.; Panchbhavi, Vinod K.
Background . A cannulated screw is currently the standard fixation method to reduce and stabilize diastasis at the lisfranc joint following injury. Currently, there is no literature examining the area of the lisfranc ligament damaged by screw placement. The objective of this investigation is to define the area of the ligament damaged by fixation with a 3.5-mm cannulated screw. Materials and Methods . Twelve cadaveric feet were dissected to identify the Lisfranc ligament metatarsal insertion site and origin on the medial cuneiform. A 3.5-mm cannulated screw was then passed over the course of the ligament and removed. The Lisfranc joint was then dissected to measure the dimensions of the ligament and damage from screw passage at the origin and insertion using imaging software. Results . Mean injury area on the metatarsal was 3.49 mm 2 and the area of injury for the cuneiform was 3.33 mm 2 . The mean percent of the area damaged was calculated to be 1.75% and 2.43% at the cuneiform and metatarsal, respectively. Conclusion . A proportionally small area of the Lisfranc ligament is disrupted following screw fixation, but the implications of this on ligament healing and outcomes remain to be elucidated. Levels of Evidence: Level V: Cadaveric study